Evaluating the impact of cooling methods on biosafety level I Escherichia coli and Bacillus cereus populations in four food products - Beardall, Lindsay M. (Kansas State University, 2016)
Food preparation in institutional settings is often carried out in large quantities. Food is cooked and then cooled and stored for later service. Improper or "slow" cooling has been identified by the United States Food and Drug Administration (US FDA) as a contributing factor in foodborne illness outbreaks. This study was designed to test the efficacy of cooling technique combinations on controlling microbial growth within pre-cooked taco meat, chili con carne with beans, low sodium marinara sauce, and brown rice food products. These products were cooked to 73.8°C (165°F) and then portioned to 2 and 3-inch depths in steam table pans. Food product was allowed to cool to 60°C ± 5°C (140°F ± 5°F) before inoculation with surrogate Escherichia coli (E. coli) or Biosafety Level I (BSL I) Bacillus cereus (B. cereus). Pans were uncovered or covered with one or two layers of aluminum foil to allow or restrict air exposure and then placed in a -20°C (-4°F) commercial walk-in freezer or situated in ice water baths in a commercial walk-in refrigerator 4°C (39.2°F). Food products were sampled over a 24-hour period (0, 4, 8, 12, and 24 hour time points) for enumeration of microbial populations. Conclusions from the cooling temperature data in this study revealed uncovered pans and pans stored in the freezer at 2-inch food product depths cooled most rapidly. However, few cooling methods achieved the two-step US FDA Food Code requirement for pre-cooked taco meat, chili con carne with beans, and brown rice products and none of the cooling methods tested achieved the US FDA food code requirement for low sodium marinara sauce. Surrogate E. coli and BSL I B. cereus microbial population data revealed pre-cooked taco meat, chili con carne with beans, and brown rice products all exhibited a certain degree of overall population decline during the 24-hour cooling period. However, a small recovery of surrogate E. coli population was observed in the low sodium marinara sauce product as well as 2-inch product depths of the chili con carne with beans product. This observed growth was less than 0.50 log₁₀ CFU/g, indicating low risk for microbial proliferation from the cooling methods tested. It is possible that the surrogate E. coli and BSL I B. cereus population changes observed were not the result of cooling failure or risk, but rather due to natural variations within the food products. These results indicate all 12 cooling methods tested were low risk and therefore effective at controlling E. coli and B. cereus microbial populations within the four food products.
Keywords: Microbiology; Food science